Recent social legislation in England - Molony, Thomas F., Sir (Statistical and Social Inquiry Society of Ireland, 1938)
Shortly after I was called to the Bar and went on the Leinster Circuit a very old member of the Circuit advised me in fatherly terms never to neglect to read the Statutes of the year because, as he said, you may be excused for not knowing a case, but you ought not to be excused for not knowing a Statute when they are brought out each year for a few shillings, and even if you hadn't the shillings you can still read them in the library or borrow them from a friend. Well, young as I was I recognised the soundness of the advice, but its value was borne in on me very strongly some years ago on reading the Report of a Scotch case in the House of Lords, where it appeared that the case was fought in the Scotch Courts and in the House of Lords, without the distinguished Scotch and English Counsel being aware of the Statute which decided the point, and it remained to be discovered by the Irish Lord of Appeal, Lord Atkinson, who no doubt in his young days had received and benefited by the same advice that I had got. From the 6th December, 1922, when I swore in my old friend Timothy Michael Healy as Governor-General of the Irish Free State, the Statutes of the Imperial Parliament ceased to apply to the Free State, and it was natural that divergencies should arise in the laws affecting the two countries, and all I propose to do in the present Paper is to sketch the course of legislation in England on certain matters of social reform, without pausing to inquire at any length on their respective merits or defects, which may well be left to our members to discuss.
Read on Wednesday, 19th January, 1938
Keywords: Social legislation; England; 314.15